An Emerging Pulmonary Haemorrhagic Syndrome in Dogs: Similar to the Human Leptospiral Pulmonary Haemorrhagic Syndrome?. (27th December 2010) - Klopfleisch, R.; Kohn, B.; Plog, S.; Weingart, C.; Nöckler, K.; Mayer-Scholl, A.; Gruber, A. D.
Abstract : Severe pulmonary haemorrhage is a rare necropsy finding in dogs but the leptospiral pulmonary haemorrhagic syndrome (LPHS) is a well recognized disease in humans. Here we report a pulmonary haemorrhagic syndrome in dogs that closely resembles the human disease. All 15 dogs had massive, pulmonary haemorrhage affecting all lung lobes while haemorrhage in other organs was minimal. Histologically, pulmonary lesions were characterized by acute, alveolar haemorrhage without identifiable vascular lesions. Seven dogs had mild alveolar wall necrosis with hyaline membranes and minimal intraalveolar fibrin. In addition, eight dogs had acute renal tubular necrosis. Six dogs had a clinical diagnosis of leptospirosis based on renal and hepatic failure, positive microscopic agglutination test (MAT) and/or positive blood/urine Leptospira -specific PCR. Leptospira could not be cultured post mortem from the lungs or kidneys. However, Leptospira -specific PCR was positive in lung, liver or kidneys of three dogs. In summary, a novel pulmonary haemorrhagic syndrome was identified in dogs but the mechanism of the massive pulmonary erythrocyte extravasation remains elusive. The lack of a consistent post mortem identification of Leptospira spp. in dogs with pulmonary haemorrhage raise questions as to whether additional factors besides Leptospira may cause this as yet unrecognized entity in dogs.